Considerations about reflexive thought and educational computing - Marcos Venícios de Oliveira Lopes; Thelma Leite de Araújo (Rev Rene)
We aim at establishing a parallel between reflexive thought and educational computing. The text is about computing misleading situations and is divided into three parts: the first summarizes the ideas of reflexive thought; the second summarizes the principles of Problem-Based Learning; and the third intends to synthesize these ideas directing them to the use in educational computing. One can notice the possibility of misleading situations and the constant encouragement of students to seek for the necessary knowledge aiming at reaching the answers demanded through computing. One concluded that the experience of making mistakes stimulates the search for the correct option and subsequent correct fixation of the contents or, at least, of the details that need to be considered to reach the correct answer.